Inflammation—The new treatment target for ischaemic stroke prevention - Gorey, Sarah; McCabe, John J.; Kelly, Peter J. (Frontiers in Stroke, 2023)
Recurrent vascular events after stroke are common despite contemporary therapies and there is an unmet clinical need for improved secondary prevention. Inflammation is a probable causal factor in first and recurrent stroke and is a promising therapeutic target. Blood biomarkers of inflammation may also improve risk stratification and patient selection for intensive prevention therapies. We review the pathogenic role of inflammation in stroke and atherosclerosis, examining data from observational and genetic studies as well as randomised controlled trials of anti-inflammatory agents in stroke and cardiac disease. We discuss the potential applications for inflammatory biomarkers in stroke care and evaluate some of the uncertainties and controversies in this field.